Trastuzumab deruxtecan: A quantum leap in HER2-positive breast cancer - Manikandan Dhanushkodi (Indian Journal of Medical and Paediatric Oncology)
Docetaxel, trastuzumab, and pertuzumab, known as THP, is the preferred first-line treatment for HER2-positive advanced breast cancer, and the second-line drug of choice is trastuzumab emtansine. Most patients eventually develop resistance to systemic therapy. Trastuzumab deruxtecan, a novel HER2-targeted antibody drug conjugate, has shown to be promising in this subset. It is a HER2-targeted antibody drug conjugate structurally composed of humanized anti-HER2 monoclonal antibody, cleavable tetra-peptide-based liker, and a potent payload (topoisomerase 1 inhibitor: Exatecan). A phase 2 trial of heavily pretreated advanced HER2-positive breast cancer (median of six lines of prior therapy) showed an overall response of 61% and a median progression-free survival of 16 months. In December 2019, the Food and Drug Administration announced accelerated approval of trastuzumab deruxtecan for HER2-positive advanced breast cancer patients who were prior exposed to two or more lines of anti-HER2 therapy in a metastatic setting.